A test method for simulating freeze-thaw cycles of steel materials in marine environments

CN122944303APending Publication Date: 2026-10-20ANGANG STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610989633.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-03
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0004]为解决钢铁材料在海水环境中冻融循环试验无法有效模拟钢铁材料在冻融过程中涉及的表面结冰行为、干湿交替腐蚀及其耦合损伤机制的问题,本发明提供了一种模拟钢铁材料在海洋环境中冻融循环的试验方法,该试验方法包括钢铁材料预处理、冻融循环、试样表征,表征结果显示,本发明公开的技术方案可以解决现有的试验方法存在的未能模拟寒带海洋环境中温度周期性交变的问题,填补钢铁材料冻融循环模拟方法的研究空白

Benefits of technology

本发明公开的技术方案通过对钢铁材料进行预处理,而后在模拟海洋环境下进行冻融循环,再对冻融循环后的试样进行表征分析,从而测试其性能,该方案可以模拟海洋冻融循环条件下钢铁材料的服役特征或腐蚀失效特征,有益于钢铁及表面防护材料在海洋冻融循环条件下的性能研究,且试验方法简单高效,具备经济性和安全性优势,可以解决现有的试验方法存在的未能模拟寒带海洋环境中温度周期性交变的问题,填补钢铁材料冻融循环模拟方法的研究空白。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention belongs to the field of materials environmental testing simulation technology, specifically relating to a test method for simulating freeze-thaw cycles of steel materials in a marine environment. The test method includes steel material pretreatment, freeze-thaw cycles, and sample characterization. The environmental simulation during the freeze-thaw cycle specifically involves placing a sample sprayed with seawater in a constant-temperature test chamber for initial low-temperature freezing, causing the sprayed solution on the sample surface to freeze. This is followed by thawing and drying, allowing the frozen ice layer on the sample surface to melt and dry. Characterization results show that the technical solution disclosed in this invention can effectively simulate the surface icing behavior, alternating wet and dry corrosion, and their coupled damage mechanisms of steel materials during freeze-thaw cycles under varying temperature conditions in a marine environment. This solves the problem of existing test methods failing to simulate the periodic temperature changes in cold-climate marine environments, filling a research gap in freeze-thaw cycle simulation methods for steel materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of material environmental testing simulation technology, specifically involving a test method for simulating the freeze-thaw cycle of steel materials in a marine environment. More specifically, it is a method for simulating the freeze-thaw cycle test of materials by simulating the marine freeze-thaw cycle environment in the laboratory. Background Technology

[0002] In frigid ocean regions, sea surface temperatures remain around 0°C year-round, with some areas experiencing winter atmospheric temperatures dropping below -50°C. Compared to mid- and low-latitude ocean regions, frigid oceans not only present a highly saline seawater corrosion environment but also experience dramatic cyclical temperature changes. When temperatures drop below freezing, seawater adsorbed on the surface of marine engineering structures, residual brine from tidal zones, or water films adhering to splash zones freeze on the steel surface. When temperatures rise above freezing, the ice melts, and corrosive liquids re-seep into the steel surface. This freeze-thaw cycle repeats itself repeatedly during the winter-spring transition in frigid ocean regions and throughout the year in some high-latitude ocean areas.

[0003] However, existing corrosion testing techniques for steel materials in marine environments have significant shortcomings. Existing marine corrosion tests mainly focus on immersion in seawater at ambient or constant temperatures. Because these tests are mostly conducted under constant temperature conditions, they fail to simulate the real-world service scenarios of cyclical temperature changes in cold-climate marine environments, thus failing to provide accurate test results and being unsuitable for actual marine environments. Freeze-thaw cycle testing has been widely applied in the building materials field. Currently, relatively mature standards for concrete freeze-thaw cycle testing, such as GB / T 50082 "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete" and ASTM C666 "Concrete Rapid Freeze-Thaw Test Method," are mainly used to evaluate the freeze-thaw resistance and durability of concrete materials under repeated freeze-thaw cycles. Concrete freeze-thaw tests typically use relative dynamic modulus of elasticity and mass loss rate as evaluation indicators, simulating the test conditions of freezing in water (-18℃ to 5℃) to evaluate the freeze-thaw resistance of the concrete material itself. However, steel materials and concrete materials have fundamental differences in physical structure and failure mechanisms. Concrete is a porous material, and its freeze-thaw damage primarily stems from the hydrostatic pressure and osmotic pressure generated by the expansion of water upon freezing in the pores. Steel, on the other hand, is a dense metallic material, and its corrosion behavior under freeze-thaw conditions is influenced by a combination of mechanisms, including electrochemical corrosion, chloride ion enrichment, and ice crystal stress damage, resulting in entirely different degradation mechanisms and failure characteristics. Therefore, directly applying existing freeze-thaw cycle testing methods in the building materials field to evaluate the performance of steel materials in marine environments is inappropriate. Currently, there is a lack of specific freeze-thaw cycle testing methods for steel materials in marine environments in China. Summary of the Invention

[0004] To address the problem that freeze-thaw cycle tests on steel materials in seawater environments cannot effectively simulate the surface icing behavior, alternating wet and dry corrosion, and their coupled damage mechanisms involved in the freeze-thaw process, this invention provides a test method for simulating freeze-thaw cycles on steel materials in marine environments. This test method includes steel material pretreatment, freeze-thaw cycles, and sample characterization. The characterization results show that the technical solution disclosed in this invention can solve the problem that existing test methods fail to simulate the periodic temperature changes in cold marine environments, filling the research gap in freeze-thaw cycle simulation methods for steel materials.

[0005] According to one aspect of the present invention, a test method for simulating freeze-thaw cycles of steel materials in a marine environment is provided, comprising the following steps: Step 1, Sample pretreatment; Step 2, freeze-thaw cycle: spray seawater solution, simulate the environment, and repeat the freeze-thaw cycle ≥ 1 time; Step 3, sample characterization; The seawater solution is a seawater solution with pH=7.0~8.5, chloride ion content of 19000~22000mg / L, alkalinity greater than 100mg / L, hardness of 6000~8000mg / L, and conductivity of 30000~50000μS / cm, which is natural seawater or self-made seawater; The spraying process is as follows: the pretreated sample is placed vertically and 2-5 ml of seawater solution is sprayed evenly using a spray bottle to simulate the environment. The environmental simulation specifically involves placing the seawater-sprayed sample in a constant temperature test chamber for low-temperature freezing, causing the solution sprayed on the sample surface to freeze, followed by melting and drying to melt and dry the frozen ice layer on the sample surface. When the simulated environment is a marine environment with winter temperatures of -40 to -5°C and summer temperatures of 5 to 15°C, the product is frozen at -40 to -5°C for 0.5 to 2 hours, and then thawed and dried at 5 to 15°C for 0.5 to 2 hours. When the simulated environment is a marine environment with winter temperatures of -70 to -20°C and summer temperatures of 5 to 15°C, the product is frozen at -70 to -20°C for 0.5 to 2 hours, and then thawed and dried at 5 to 15°C for 0.5 to 2 hours. When the simulated environment is a marine environment with winter temperatures of -20 to -5°C and summer temperatures of 25 to 40°C, the sample is frozen at -20 to -5°C for 0.5 to 2 hours, and then thawed and dried at 25 to 40°C for 0.5 to 2 hours.

[0006] Based on the above technical solution, the pretreatment includes processing and polishing, sanding, alkaline degreasing and / or hydrophobic modification or coating treatment.

[0007] Based on the above technical solution, the processing and polishing specifically involves: processing the sample into a parallel sample with dimensions of 30~50×30~50×3~10mm, and then polishing it with sandpaper until the surface is uniform.

[0008] Based on the above technical solution, the sample used for sample pretreatment is a steel material, which is selected from one of the following: shipbuilding steel, marine engineering steel, bridge steel, and construction steel.

[0009] Based on the above technical solution, the steel material is selected from one of the following: shipbuilding steel A, AH32, AH36, EH36, FH36, marine engineering steel VL4-4, and bridge steel Q420qE.

[0010] Based on the above technical solution, the alkaline degreasing specifically involves using an alkaline solution with a concentration of 20-50 g / L to degrease the sample after sanding; the alkaline solution is selected from at least one of sodium hydroxide, sodium carbonate, trisodium phosphate, and sodium metasilicate, preferably a mixed solution of sodium hydroxide and sodium bicarbonate, a mixed solution of sodium hydroxide and trisodium phosphate, or a solution of sodium hydroxide, trisodium phosphate, and sodium metasilicate.

[0011] Based on the above technical solution, the hydrophobic modification specifically involves: performing hydrophobic modification on the sample after degreasing treatment, wherein the modifier is selected from at least one of hydrochloric acid, ferric chloride, copper sulfate, stearic acid, ethanol, and water, and the modification conditions are: soaking in the modifier for 0.5 to 6 hours.

[0012] Based on the above technical solution, the coating treatment specifically involves coating the sample after degreasing, wherein the coating is selected from at least one of metal coating, organic coating, and inorganic / composite coating, and the coating thickness is 5~200μm.

[0013] Based on the above technical solution, the sample characterization includes morphological observation, corrosion electrochemical testing, corrosion weight loss calculation, hydrophobicity characterization, and durability characterization.

[0014] Beneficial effects The technical solution disclosed in this invention pre-treats steel materials, then subjectes them to freeze-thaw cycles in a simulated marine environment, and finally characterizes and analyzes the samples after freeze-thaw cycles to test their performance. This method can simulate the service characteristics or corrosion failure characteristics of steel materials under marine freeze-thaw cycles, which is beneficial to the performance research of steel and surface protection materials under marine freeze-thaw cycles. Moreover, the test method is simple and efficient, with economic and safety advantages. It can solve the problem that existing test methods fail to simulate the periodic temperature changes in cold marine environments, and fill the research gap in the simulation method of freeze-thaw cycles for steel materials. Attached Figure Description

[0015] Figure 1A schematic diagram of an experimental method to simulate freeze-thaw cycles of steel materials in a marine environment; Figure 2 The corrosion electrochemical impedance spectroscopy diagram for Example 1; Figure 3 This is a graph showing the change of water contact angle with the freeze-thaw cycle in Example 2. Detailed Implementation

[0016] To make the objectives and technical solutions of this invention clearer, the following embodiments are provided for further explanation. However, the scope of protection of this invention is not limited to these embodiments; the embodiments are merely for illustrative purposes. Those skilled in the art should understand that any changes or equivalent substitutions that do not depart from the concept of this invention are included within the scope of protection of this invention.

[0017] Unless otherwise specified, all reagents and raw materials used in this invention are obtained through purchase.

[0018] In Example 2 of this invention, the concentration of ferric chloride in the hydrochloric acid / ferric chloride / aqueous solution is 10 wt%, the mass ratio of HCl to FeCl3 is 1:1, the concentration of stearic acid in the stearic acid / ethanol solution is 0.05 mol / L, and the concentration of copper sulfate aqueous solution is 0.05 mol / L.

[0019] Example 1: A test method simulating freeze-thaw cycles of steel materials in a marine environment is disclosed. This method is used to conduct freeze-thaw cycle tests on marine steel in a simulated Arctic Ocean environment and to analyze the corrosion electrochemical behavior of the steel materials after the freeze-thaw cycle test. The samples used are marine steels AH36, EH36, and FH36. Parallel samples were machined to a size of 50×50×10mm and successively polished with 200#, 600#, and 1000# sandpaper until the surface was uniform. Surface oil was removed with an alkaline solution (a 20g / L mixed solution of sodium hydroxide and sodium bicarbonate, with a mass ratio of sodium hydroxide to sodium bicarbonate of 1:1). After sample pretreatment, 100 freeze-thaw cycles were initiated. During each freeze-thaw cycle, a 3.5wt% sodium chloride solution (pH=7.0, chloride ion content 2176) was sprayed as the seawater solution. (0 mg / L, alkalinity 120 mg / L, hardness 6000 mg / L, conductivity 45000 μS / cm) The sample was placed vertically, and an equal volume of solution (2 mL) was sprayed evenly using a spray bottle. The parallel samples were then placed in a constant temperature test chamber with the ambient temperature set to -40°C (average winter temperature of the Arctic Ocean) for 0.5 hours, allowing the sprayed solution on the sample surface to freeze. Subsequently, the ambient temperature was set to 5°C (average summer temperature of the Arctic Ocean) for 2 hours, allowing the frozen layer on the sample surface to melt and dry. The samples were then removed, and the next freeze-thaw cycle was initiated. After 100 freeze-thaw cycles, the parallel samples were removed for corrosion electrochemical performance analysis to evaluate the corrosion electrochemical performance of steel materials under simulated marine freeze-thaw cycle conditions. The AC impedance spectra of the samples showed that after freeze-thaw cycles, the AC impedance radii of the three types of marine steel were all relatively small. The test performance is shown in the figure. Figure 2 .

[0020] Example 2: A test method for simulating freeze-thaw cycles of steel materials in a marine environment is used to conduct freeze-thaw cycle tests on the superhydrophobic modified surface of marine steel VL4-4 in a simulated Antarctic marine environment, and to analyze the hydrophobic properties of the modified surface after the freeze-thaw cycle test. The samples used were marine engineering steel VL4-4. Parallel samples were machined to a size of 40×40×5mm and polished sequentially with 200#, 600#, and 1000# sandpaper until the surface was uniform. Surface oil was removed with an alkaline solution (a 50g / L mixed solution of sodium hydroxide and trisodium phosphate, with a mass ratio of sodium hydroxide to trisodium phosphate of 10:1). Three different methods (etching, deposition, and coupling) were used to modify the surface for superhydrophobicity. (For etching, the etching modification solution was a 1:1 mass ratio of hydrochloric acid / ferric chloride / aqueous solution and stearic acid / ethanol solution, with an immersion time of 2 hours; for deposition, the deposition solution was a 1:1 mass ratio of copper sulfate aqueous solution and stearic acid / ethanol solution, with an immersion time of 1 hour; for coupling, the coupling modification solution was a combination of the etching modification solution and the deposition solution.) The mass ratio of the etching modification solution to the sedimentation solution was 1:1, and the immersion modification time was 3 hours. After the sample pretreatment was completed, 20 freeze-thaw cycles were started. In each freeze-thaw cycle, the sprayed seawater solution was Bohai Sea water (pH=8.1, chloride ion content 19800mg / L, alkalinity 295mg / L, hardness 7500mg / L, conductivity 47000μS / cm). The sample was placed vertically, and an equal amount of solution was sprayed evenly using a spray bottle, with a spray volume of 3mL. Then, the parallel samples were placed in a constant temperature test chamber, and the ambient temperature was set to -70℃, the winter temperature of the Antarctic inland marginal sea area, for a freezing time of 0.5 hours, so that the solution sprayed on the sample surface would freeze. Then, the ambient temperature was set to 5℃, the summer temperature of Antarctica, for a thawing and drying time of 1.5 hours, so that the ice layer on the sample surface would melt and dry. Then, the sample was taken out, and the next freeze-thaw cycle was started. After 50 freeze-thaw cycles, parallel samples were taken out for hydrophobicity analysis to evaluate the hydrophobicity of the steel-modified surface material under simulated marine freeze-thaw cycle conditions. Test results are shown below. Figure 3 Analysis shows that the hydrophobic properties of the superhydrophobic modified surface are maintained under freeze-thaw cycles.

[0021] Example 3: A test method simulating freeze-thaw cycles of steel materials in a marine environment is disclosed. This method is used to conduct freeze-thaw cycle tests on the organic coating on the surface of bridge steel Q420qE in a simulated marine environment of the Bohai Sea, and to analyze the durability of the coating on the steel material surface after the freeze-thaw cycle test. The test specimens used are bridge steel Q420qE. The specimens are processed into parallel specimens with dimensions of 50×50×10mm, and then polished sequentially with 200#, 600#, and 1000# sandpaper until the surface is uniform. Surface oil contamination is removed with an alkaline solution (a 30g / L solution of sodium hydroxide / trisodium phosphate / sodium metasilicate, wherein the mass ratio of sodium hydroxide, trisodium phosphate, and sodium metasilicate is 8:1:1). An organic epoxy coating (zinc-rich epoxy coating, 125μm thick) is then applied to the surface. After the specimen pretreatment, 50 freeze-thaw cycles are performed. During each freeze-thaw cycle, a seawater solution containing 3.0wt% sodium chloride is sprayed. A solution (pH=7.0, chloride ion content 21760 mg / L, alkalinity 120 mg / L, hardness 6000 mg / L, conductivity 45000 μS / cm) was used. The sample was placed vertically, and an equal volume of solution (5 mL) was sprayed evenly using a spray bottle. The parallel samples were then placed in a constant temperature test chamber with the ambient temperature set to -5°C (average winter temperature in the Bohai Sea) for 2 hours, allowing the sprayed solution on the sample surface to freeze. Subsequently, the ambient temperature was set to 25°C (average summer temperature in the Bohai Sea) for 1 hour, allowing the frozen layer on the sample surface to melt and dry. The samples were then removed, and the next freeze-thaw cycle was initiated. After 50 freeze-thaw cycles, the parallel samples were removed for durability analysis. The calculated sample mass loss rate was only 0.23%, demonstrating that the surface organic coating possesses good durability under freeze-thaw cycle conditions. The periodic freeze-thaw cycles did not damage the organic coating.

[0022] Comparative example: The standard GB / T 43356-2023 "Cyclic Immersion Test Method for Corrosion of Steel Bars in Salt Solution" or TB / T 2375-1993 "Cyclic Immersion Corrosion Test Method for Weathering Steel for Railways" is used to conduct cyclic corrosion tests on steel for shipbuilding, marine engineering, and bridges. The corrosion electrochemical performance, hydrophobicity, and durability performance after the test are then tested. This method can only conduct cyclic immersion tests at constant temperature and cannot simulate the effect of freeze-thaw cycles under alternating temperature conditions.

[0023] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A test method for simulating freeze-thaw cycles of steel materials in a marine environment, comprising the following steps: Step 1, Sample pretreatment; Step 2, freeze-thaw cycle: spray seawater solution, simulate the environment, and repeat the freeze-thaw cycle ≥ 1 time; Step 3, sample characterization; The seawater solution is a seawater solution with pH=7.0~8.5, chloride ion content of 19000~22000mg / L, alkalinity greater than 100mg / L, hardness of 6000~8000mg / L, and conductivity of 30000~50000μS / cm, which is natural seawater or self-made seawater; The spraying process is as follows: the pretreated sample is placed vertically and 2-5 ml of seawater solution is sprayed evenly using a spray bottle to simulate the environment. The environmental simulation specifically involves placing the seawater-sprayed sample in a constant temperature test chamber for low-temperature freezing, causing the solution sprayed on the sample surface to freeze, followed by melting and drying to melt and dry the frozen ice layer on the sample surface. When the simulated environment is a marine environment with winter temperatures of -40 to -5°C and summer temperatures of 5 to 15°C, the product is frozen at -40 to -5°C for 0.5 to 2 hours, and then thawed and dried at 5 to 15°C for 0.5 to 2 hours. When the simulated environment is a marine environment with winter temperatures of -70 to -20°C and summer temperatures of 5 to 15°C, the product is frozen at -70 to -20°C for 0.5 to 2 hours, and then thawed and dried at 5 to 15°C for 0.5 to 2 hours. When the simulated environment is a marine environment with winter temperatures of -20 to -5°C and summer temperatures of 25 to 40°C, the sample is frozen at -20 to -5°C for 0.5 to 2 hours, and then thawed and dried at 25 to 40°C for 0.5 to 2 hours.

2. The test method according to claim 1, characterized in that, The sample used for the sample pretreatment is a steel material, which is selected from one of the following: shipbuilding steel, marine engineering steel, bridge steel, and construction steel.

3. The test method according to claim 1, characterized in that, The pretreatment includes processing and polishing, sanding, alkaline degreasing, hydrophobic modification, or coating treatment.

4. The test method according to claim 3, characterized in that, The specific processing and polishing process involves processing the sample into a parallel sample with dimensions of 30~50×30~50×3~10mm, and then polishing it with sandpaper until the surface is uniform.

5. The test method according to claim 3, characterized in that, The alkaline degreasing process specifically involves using an alkaline solution with a concentration of 20-50 g / L to degrease the sample after sanding. The alkaline solution is selected from at least one of sodium hydroxide, sodium carbonate, trisodium phosphate, and sodium metasilicate.

6. The test method according to claim 3, characterized in that, The hydrophobic modification specifically involves: performing hydrophobic modification on the sample after degreasing treatment, with the modifier selected from at least one of hydrochloric acid, ferric chloride, copper sulfate, stearic acid, ethanol, and water, and the modification conditions being: soaking in the modifier for 0.5 to 6 hours.

7. The test method according to claim 3, characterized in that, The coating process specifically involves applying a coating to the degreasing sample. The coating is selected from at least one of metal coatings, organic coatings, and inorganic / composite coatings, and the coating thickness is 5~200μm.

8. The test method according to claim 1, characterized in that, The sample characterization includes morphological observation, corrosion electrochemical testing, corrosion weight loss calculation, hydrophobicity characterization, and durability characterization.